КУЛЬТУРНО-ПРОСВІТНИЦЬКА ДІЯЛЬНІСТЬ МОЛОЧАНСЬКОГО МЕНОНІТСЬКОГО УЧИТЕЛЬСЬКОГО ТОВАРИСТВА НА ПОЧАТКУ ХХ ст. (Zaporizhzhia Historical Review, 2021)
The cultural and educational activity of the Molochansík Mennonites Teachers Society early in the 20th century are investigated in the article. The role of the church institutions in the Mennonites educational system is described. The author presents the main forms of the Molochansík Mennonites Teachers Society activities.